Megafauna from sublittoral to abyssal depths along the Mid-Atlantic Ridge south of Iceland - Copley, Jtp; Tyler, Pa; Sheader, M; Murton, Bj; German, Cr (Gauthier-Villars, 1996)
101 species were identified from 102 biological samples obtained between 225 and 2600 m depth on the Reykjanes Ridge, extending the biogeographic records for several species. Multivariate analysis of between-sample species similarity reveals a two-zone bathymetric faunal distribution with the transition at 800-1000 m. A hydrographic survey of the ridge axis suggests that this faunal zonation is influenced by the water mass structure. Despite the limitations of a sampling programme not designed a priori for biological sampling, the recovery and preservation of the samples and the insight that they provide serves to reinforce that every effort should be made to capitalise on the opportunities for obtaining samples afforded by non-biological sampling programmes.